PENERAPAN MODEL COOPERATIVE LEARNING TIPE NUMBERED HEAD TOGETHER (NHT) DALAM MENINGKATKAN HASIL BELAJAR IPS - aprizan -; Erminis - (LP3M STKIP Muhammadiyah Muara Bungo, 2018)
The background of the problem in this study was the low learning outcomes on social subject of fourth grade students of SD Negeri 81/II Muara Bungo. This study aimed to describe the process and results of social subject by applying Cooperative Learning called Numbered Head models in grade IV SD Negeri 81/II Muara Bungo.This research was a Classroom Action Research (CAR) with four stages of activities namely planning, action, recognition and reflection. The results of the data analysis have shown that the application of the Numbered Head Together could improve the process and results of social subject grade IV SD Negeri 81/II Muara Bungo.